Extended Extragradient Methods for Generalized Variational Inequalities - Yonghong Yao; Yeong-Cheng Liou; Cun-Lin Li; Hui-To Lin (Journal of Applied Mathematics)
We suggest a modified extragradient method for solving the generalized variational inequalities in a Banach space. We prove some strong convergence results under some mild conditions on parameters. Some special cases are also discussed.